Approach to endoscopic procedures during COVID-19 pandemic – not as expected - Ratyński, Tomasz; Bednarczuk, Arkadiusz; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2020)
The SARS-CoV-2 epidemic and ensuing transformation of the Central Clinical Hospital of the Ministry of the Interior and Administration in Warsaw into one of the largest specialist infection disease hospitals in Poland imposed a complete reorganisation of work, including in the endoscopy unit. For the vast majority of hospitalised patients, COVID-19 infection posed an extra burden in addition to already known and treated chronic disorders. Therefore, the work schedule and infrastructure have been rearranged in order to minimise the risk of transmission of infection to the personnel as well as to ensure continuous preparedness to perform all endoscopic procedures in patients infected with or suspected of SARS-CoV-2 infection. Between 16.03.2020 and 20.07.2020 we performed 91 endoscopic procedures involving the upper and lower gastrointestinal tract. The majority of those procedures were performed for urgent indications and as a part of on-call duties. The scope of endoscopic procedures was much broader than initially anticipated at the beginning of the epidemic, indicating the need for a change in the recommendations in that regard. Thanks to the application of appropriate procedures and personal protective equipment (PPE) there were no cases of infection among the employees of the Endoscopy Unit coming in direct contact with patients during the above-mentioned period.